The explanation of the main characteristics of penal populism and examples of penal populism in some criminal law provisions and planned amendments of the Criminal Code of Serbia - Škulić Milan; Lukić Natalija (Crimen (Beograd), 2025)
The article explains the main characteristics of penal populism as one very interesting criminological phenomenon and the basic manifestations of penal populism in some amendments and provisions of the Criminal Code of Serbia. This is especially reflected in some areas of criminal-justice legislation: 1) Introducing the prohibition of mitigating the penalty for certain types of criminal offences; 2) Introducing the institute of multiple recidivism; 3) Significant limitation on possibilities of suspended sentencing; 4) Prescribing a lifetime imprisonment, in combination with introducing a legal prohibition on release on parole for certain categories of offenders sentenced to this penalty. The paper also explains that the current Criminal Code of Serbia has been frequently amended and supplemented by numerous amendments. Some of these amendments of the Criminal Code of Serbia, culminating in the amendments from 2019, also contain elements of penal populism. The authors present an argumentative critique of the superfluous elements of penal populism within the Serbian Criminal Code, which are also evident in some of the proposed amendments. That tendency is also not in accordance with the prevailing understandings of modern criminal law, criminology, penology, or criminalistic doctrine, nor, more importantly, is such an approach of the legislator in line with the current state of crime rates and the need to respond to it in an adequate manner. The article explains that populist penal provisions prescribed in the Serbian Criminal Code, as well as in the proposed amendments to the country's criminal legislation, directly contradicts Serbia's official efforts to strengthen the system of alternative criminal sanctions aimed at reducing prison overcrowding. Moreover, in certain respects, it conflicts with the restorative justice framework that Serbia has adopted. These contradictions provide a compelling reason to reconsider several provisions of the Criminal Code. Authors especially conclude that a judge in a country characterized by the rule of law must still have the strength to resist such "public expectations" and to make his decision in accordance with the law and according to his free conviction and of course, the judge must also resist the influence of criminal populism promoted in the media or by some politicians, even other public figures/persons, etc., but a special problem arises when elements of criminal populism penetrate in the criminal legislation.